3D Printing: Solvent‐Cast Three‐Dimensional Printing of Multifunctional Microsystems (Small 24/2013). Issue 24 (20th December 2013) - Guo, Shuang‐Zhuang; Gosselin, Frédérick; Guerin, Nicolas; Lanouette, Anne‐Marie; Heuzey, Marie‐Claude; Therriault, Daniel
<x xml:space="preserve">Abstract</x> Various microstructures including straight filaments, layer‐by‐layer scaffolds and freeform helical spirals are fabricated by a solvent‐cast three‐dimensional printing technique, as reported by D. Therriault and co‐workers on page 4118. The fabrication capabilities of this powerful and flexible process are demonstrated by the printing of three microsystems featuring mechanical, microfluidic and electrical functionalities, such as a high‐toughness microstructured fiber, a 3D microchannel and a Ka band antenna. These capabilities can be extended through the utilization of other thermoplastic‐based inks and the printing of features at the sub‐micrometer‐ and potentially nanoscale. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>